Work Predictors of Lapse in Patients under Treatment of ‎Methadone Maintenance Therapy - Ramin Mehrdad; Benafsheh Zarbafi; Gholamreza Pouryaghoub; Maryam Saraeei (Iranian Journal of Psychiatry, 2016)
Background: Addiction to narcotics ‎can cause serious problems and ‎monetary losses. Therapeutic ‎success can be predicted ‎through identifying lapse risk ‎factors.‎ Objective: Determining Job Risk ‎Factor of Lapse.‎ Methods: This was a cross ‎sectional study on 351 addicts ‎visiting five methadone clinics. A ‎Data collection sheet consisting ‎of questions on demographic ‎and job information was filled up ‎through direct interviews. ‎Information relating to lapse in ‎the first month was analyzed.‎ Results: The mean (SD) age of ‎the participants was 40(12) ‎years; of them, 74% were ‎employed, of whom 34% had ‎lapsed. A relationship was ‎noticed between education ‎qualification (secondary school ‎compared with higher and lower ‎education) and lapse (p = .04), ‎and also between type of drug ‎abuse (amphetamine) and lapse ‎‎(p = .001).‎ Conclusion:‎‏ ‏‎ Lapse was more ‎dependent on type of drug abused, ‎and employment had a protective role, ‎with no correlation with the type of ‎job and other job conditions. Non-‎work factors mediated/suppressed the ‎role of occupational conditions.‎